P47 Modified blalock-taussig shunts versus ductal stenting in duct dependent cyanotic congenital heart defects. (2nd March 2016) - Zava, Ngonidzashe K; Bentham, J; Thompson, John
Abstract : Objective: To compare early post procedure outcomes, angiographic and intervention findings and 30 day survival between two groups of infants with duct dependent congenital heart disease; palliation with a Blalock-Taussig Shunt (mBTS) or with a ductal stent (DS). Ductal stenting is an emerging catheter therapy obviating the need for neonatal surgery and allowing palliation through to reparative surgery or subsequent cavo-pulmonary palliation later in infancy. Methods: This retrospective cohort study was performed between July 2012 and July 2015. 39 patients underwent palliation during this period. 25 received a mBTS and 14 underwent ductal stent placement. Primary and secondary outcomes were survival and need for cardiac re-intervention up to reparative or subsequent palliative surgery. Results: There was no difference in 30 day or one year survival between the two groups (30-day, 100% mBTS vs. 93% DS, p = 0.34; 1 year, 96% mBTS vs. 86% DS, p = 0.23). Re-intervention rates with need for a further mBTS, angioplasty+/- re-stent prior to reparative repair or cavo-pulmonary palliation was also similar between the groups (16% mBTS vs. 21% DS, p = 0.67). Pulmonary artery dimensions prior to subsequent surgery showed a non significant higher Nakata Index in the mBTS group compared to the DS group, (mean Nakata Index (Cl), mBTS 275 (210–342) vs 203 (152–253) P = 00.141). Oxygen saturations and haemoglobin level were similar across both groups. There was a similar need for pulmonary artery reconstruction at the time of subsequent surgery for both groups. There was a non-significant trend to earlier repair for the DS group (328 days mBTS vs. 234 days DS). Conclusions: DS is a viable alternative to placing a mBTS for neonatal palliation of cyanotic congenital heart disease achieving similar outcomes. There remains concern about the longevity of DS with a need for earlier subsequent surgery and very close follow-up.